(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The main objective of the study was to determine the effects of COVID-19 pandemic on yam production in Taraba State. A total of 120 respondents were purposively selected from 8 village communities of 4 local government areas of the state. The local government areas were: Wukari, Ibbi, Yorro and Zing. Data were collected on both socio-economic and farm characteristics of the respondents. Other areas include: perceived effect of COVID-19 pandemic on yam production, information needs of the respondents during COVID-19 pandemic, and constraints to adaptation strategies experienced by the respondents during COVID-19 pandemic. Data collected were analyzed using frequency and percentages, mean score, standard deviation and factor analysis. The result of the analysis revealed that the majority (72.5%) of the respondents were males and married (68.3%) and the farmers mean age was 35 years. The mean household size of the respondents was 5 persons. The pandemic had negatively affected yam production in the study area and led to decline in farm income, shortage of input supply, general outbreak of yam beetle disease. Information needs of the respondents includes: access to marketing, access to fertilizer, access to credit. Major constraints encountered by the respondents in adapting to the adverse effect of the pandemic include high cost of labour, communication/ language barrier in getting information about COVID-19 pandemic, and diversion of COVID-19 pandemic palliative meant to cushion the adverse effect of the pandemic. It was recommended that government should strengthen early warning and surveillance systems to detect and monitor emerging infectious diseases.